WORK WITH MUSICALLY GIFTED STUDENTS IN PEDAGOGICAL PROFESSIONAL COLLEGE - Давиденко, А. (SWorldJournal, 2022)
In theses statements have been actualized the features of working with musically gifted students of the pedagogical professional college, offered methodological recommendations for identifying and developing the musical abilities of gifted education appli